Consuming space : placing consumption in perspective - Goodman, Michael K., 1969-; Goodman, David, 1938-; Redclift, M. R. (Ashgate, 2010)
Emerging from a series of seminars on 'Cultures of Consumption' which encouraged a robust interdisciplinary debate, this volume focuses on the temporal and spatial dimensions of consumption. The contributors specifically explore the changing dimensions of consumption as networking across temporal and transcultural contexts. In considering spaces and places of consumption, it explores how these are delineated and scaled over time, and how the politics of scale play out over the changing networked relationships of local, national, transnational and globalized consumption spaces. In these spatial processes, the role of 'place' can become both fixed and malleable. In some cases, 'placed' commodities appear to act at a distance, acquiring value and 'reputation', while in other cases, commodity biographies of place are suppressed by mechanisms of displacement. A team of leading scholars from the USA, UK and Latin America analyze the different orderings of the 'power of space' in the historical, material and cultural constructions of consumption. In doing so, the book also questions the way the changing nature of consumption is dealt with theoretically and conceptually across space, place and time and the complicity of this analysis.